THE IMPACT OF THE ACTIVE NATION PROGRAM AS A SOCIO-CULTURAL PRACTICE FOR INCREASING PHYSICAL ACTIVITY AMONG 13-YEAR-OLD DISPLACED SCHOOLCHILDREN IN UKRAINE - Galan, Y. P.; Yarmak, O. M.; Moseichuk, Y. Y. (My University, 2025)
The article presents an analysis of the impact of the ACTIVE NATION program on increasing the level of physical activity and physical fitness of 13-year-old displaced schoolchildren in Ukraine under martial law.The purpose of this study is to determine the effectiveness of the ACTIVE NATION program as a sociocultural practice aimed at increasing physical activity and developing motor skills in 13-year-old displaced schoolchildren in Ukraine.Research methods. The article presents the results of a study on the impact of the ACTIVE NATION program on the physical fitness and level of physical activity of 13-year-old adolescents in conditions of martial law. There were 34 displaced school kids studying at general education schools in Chernivtsi who took part in the teaching experiment. Only male teens were involved in the study because this subgroup had the most students who signed up to take part in the teaching experiment during recruitment. The fol-lowing methods were used: analysis and generalization of scientific and methodological literature, docu-mentary materials, logical and theoretical analysis, comparative analysis, synthesis and systematization, pedagogical diagnostics using methods of systematic observation and testing, sociological approaches, and mathematical statistics. Results. The results of the study confirm the high effectiveness of the ACTIVE NATION program in promoting a healthy and active lifestyle among 13-year-old adolescents. Positive changes were recorded in the ALPHA-Fitness test indicators, which characterize endurance, coordination, and flexibility. The median result of the “20 m shuttle run” test increased from 5.9 segments to 6.7 segments, which is a 13.5% increase in efficiency (p < 0.05). In the EUROFIT test, the number of errors in the Flamingo balance test decreased by 11.8% (p < 0.05), and the result in the Sit and Reach exercise increased by 14.3% (p < 0.05). The assessment of motor tests and PAQ-A showed an increase in daily activity and improvement in motor skills. The results can be explained by the complex components of the program, implemented through events, competitions, and the participation of famous athletes. Even in the school environment, activity during breaks increased by 50.0% (p < 0.01).Conclusions. The results confirm the effectiveness of the ACTIVE NATION program in improving the physical fitness and daily physical activity of 13-year-old adolescents, demonstrating the feasibility of implementing such comprehensive approaches in the context of the current crisis.
Keywords: ALPHA-Fitness; EUROFIT; displaced schoolchildren; physical activity; program; social culture